Ryte i wydrapywane motywy na wczesnośredniowiecznych i wczesnonowożytnych naczyniach z Ostrowa Tumskiego w Poznaniu - Antowska-Gorączniak, Olga; Kóčka-Krenz, Hanna; Sikorski, Andrzej (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2020)
During excavations carried out in Ostrów Tumski by the Institute of Prehistory of the Poznań University, a small collection of utensils was found with incised or scratched motifs which are reminiscent of decorations (Figure1). The collection includes an early medieval mug (9th – mid-10th c.; Figure 2:1) as well as jars and a plate (?; 16th c.; Figure 2:2-4) with mysterious signs placed on the receptacles before they were fired (incisions: receptacle 1 and 4) and in the course of use thereof (scratched with a sharp object: receptacle 2 and 3). They were excavated in the ducal garden next to the palace and sacral complex (receptacle 1) and the Gothic St. Mary’s church and the adjacent cemetery (receptacle 2) as well as in the northern part of the island (receptacles 3 and 4). They were excavated from cultural layers (receptacle 1), from a well’s thill (receptacle 2), a wooden waste pond where fish were kept (?; receptacle 4) and a backfill of another well (receptacle 3). On the early medieval mug, where the neck becomes a body, it the middle of its circumference, parallel to the receptacle’s edge, there are signs in the form of a vertical line, a square, another vertical line topped with tiny parallel incisions and two crossing lines incised with a sharp object in a dried utensil before it was fired (Figure 3:1). On the upper part of the body of an almost completely preserved jar, four crossing lines were scratched to form a star, a loop, three intersecting lines – a star, the letter “Y” with three perpendicular lines in the lower part and, slightly lower, a boat /a crescent (?; Figure 3:2). On another jar, in the upper part of its body, next to the handle, a sharp object was used to scratch an inscription made of 6-7 “letters” (Figure 3: 3). At the bottom of a bowl (?), a potter incised with a sharp object a lily and an anchor cross. While only four specimens have been excavated in Ostrów Tumski in Poznań, and the signs are hard to interpret, an attempt can be made to explain the reasons why they were placed on the receptacles. The incisions on two of them were made before the receptacles were fired, hence they can be attributed to the potters’ work. In the case of the mug (Figure 2:1; 3:1), the fact that it was made by the same person was emphasized. The act of incising the bottom of the other utensil (Figure 2:4; 3:4) may have somethingto do with it being made for a specific group of users. On the other hand, the two remaining receptacles were scratched when they were ready so they were marked by the owners at the expense of the utensils’ looks. The jug was preserved almost intact (Figures 2:2; 3:2; 4) and could hold 2 litres of liquid. It is covered with symbols meaningful to its owner, perhaps identifying him/her. A piece of the jug (Figures 2:3, 3:3) bears an inscription which, with some caution, may be interpreted as dialectal words of German or Dutch origin, meaning “my (drinking) utensil”. Irrespective of the correctness of “deciphering” the scratched signs, these are undoubtedly unique hand-written inscriptions from the second half of the 16th century. If anything, it is a good reason to devote attention to them.